2010
DOI: 10.1111/j.1742-6723.2010.01298.x
|View full text |Cite
|
Sign up to set email alerts
|

Review article: Safety profile of propofol for paediatric procedural sedation in the emergency department

Abstract: The use of propofol for paediatric procedural sedation (PPS) is increasing because of its favourable pharmacodynamic profile. Its paediatric use has been limited in some ED (emergency departments) because of the perceived high rate of serious adverse events in comparison with other sedation agents. A systematic literature review of propofol use for PPS outside the operating theatre environment from 1966 to 2008 was carried out to profile the adverse event rate in comparison with other procedural sedation agent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 108 publications
0
16
0
4
Order By: Relevance
“…From 2,882 unique references, 14 completed systematic reviews were included (Figure , Table ). Three protocols for in‐process reviews were identified on propofol and midazolam for procedural sedation and structured sedation programs in acute care settings; since the protocols provide no data they are not included in this review.…”
Section: Resultsmentioning
confidence: 99%
“…From 2,882 unique references, 14 completed systematic reviews were included (Figure , Table ). Three protocols for in‐process reviews were identified on propofol and midazolam for procedural sedation and structured sedation programs in acute care settings; since the protocols provide no data they are not included in this review.…”
Section: Resultsmentioning
confidence: 99%
“…B. Propofol als Sedativum und einem zusätzlichen Analgetikum (z. B. Ketamin) in der Mehrzahl der kardiologischen Zentren bereits seit Jahren klinischer Standard [3] und in den kinderkardiologischen Zentren seit Jahren gelebte Praxis ist [2,[4][5][6]…”
Section: Kinderkardiologische Patienten Tolerieren Diagnostische Und unclassified
“…Tiefe Analgosedierungen (≥Stufe III) erfordern für die Durchführung und Überwachung weitere, entsprechend qualifizierte personelle Unterstützung. Auf das bereits in der Kardiologie als effektiv und sicher etablierte sowie in den meisten kinderkardiologischen Zentren in der klinischen Praxis genutzte Konzept der "nurse-administered propofol sedation" wird ausdrücklich hingewiesen (NAPS, [3,6] Bei Gesundheitspflegern und -pflegerinnen mit Fachweiterbildung Intensivpflege oder Anästhesie oder auch langjährig erfahrenen Pflegern/Pflegerinnen im Bereich Kinderkardiologie bzw. Intensivmedizin kann von diesen erforderlichen Kenntnissen und Erfahrungen ausgegangen werden.…”
Section: Personal Und Zuständigkeitunclassified
“…It can be used for short, painful procedures in combination with analgesia. Adverse events were rare in two paediatric series, with reported complications of hypotension (15.4%), desaturation (9.3%), apnoea (1.9%), assisted ventilation (1.4%), unplanned intubation (0.2%), emesis(0.14%), laryngospasm (0.1%), bradycardia (0.1%) and anaphylaxis in children with egg or soy allergies …”
Section: Pharmacological Sedationmentioning
confidence: 99%